STUDI PENGGUNAAN BAHAN TAMBAH KOAGULAN “AMPO’ PADA PENGOLAHAN LIMBAH DOMESTIK YANG MENGANDUNG DETERJEN DENGAN PROSES KOAGULAI FLOKULASI - Nilna Amal (Universitas Lambung Mangkurat, 2006)
The principles of wastewater treatment is to convert the objectionable material to less objectionable form, to dispers the pollutants so that their concentration are minimal, or to concentrate them for isolating them from the environment. Detergent content in domestic wastewater disposal has different characteristics from the others thereby they need special approach to remove from the effluent. This research intend to recognize whether there is correlation between detergent content and the other water quality parameters. Thereafter tried to treat domestic wastewater with coagulation flocculation process use alum as coagulant and dry clay which called “Ampo” as coagulant aid, then rapid mixing is conducted along 5 minutes, this process continue with sedimentation.This research is conducted in laboratory scale use simulation water. Detergent content varies from 20 mg/l to 180 mg/l. The parameters are pH, Total Dissolved Solid (TDS) and KMnO4. Research finding shows that there is linear correlation between detergent content with pH and TDS, for KMnO4 the correlation undefinitive. It also found that there are increasing water quality that indicated with decreasing parameters after the treatment.